ASSESSMENT OF THE WATER QUALITY OF THE SUPPLY SYSTEM OF A MUNICIPALITY (Cadernos ESP, 2023)
To analyze the microbiological and physical-chemical patterns of the analyzes of samples collected from the Water Supply Systems - SAA of a municipality in Ceará. A descriptive, quantitative retrospective investigation was carried out, from January 2018 to December 2022, of the results of the analyzes carried out by the Central Public Health Laboratory of Ceará (LACEN-CE), unit of Juazeiro do Norte-CE, regarding microbiological and physical-chemical patterns of the supply systems of a municipality in Ceará, using the Information System for the Surveillance of Water Quality for Human Consumption (SISAGUA) as a data collection instrument. The variables studied were Total Coliforms (CT ), Escherichia coli and Turbidity, following the potability standards recommended by Consolidation Ordinance No. 5/2017 MS. It was found that the analyzed variables showed samples outside the allowed standards during the evaluated period, in at least one of the years that make up the historical series studied. The Total Coliforms pattern showed the highest percentage and the highest annual frequency of samples in non-compliance with the aforementioned ordinance. The results of the study suggest that immediate and effective actions are needed to improve the execution of monitoring and the quality of water for human consumption in the municipality where the study was carried out, in order to guarantee the health of the population.
Keywords: Water supply; Monitoring; Potability; Water quality